Nanoformulation and Preclinical Evaluation of Dihydroartemisinin–Lumefantrine and Primaquine as Combined Antimalarial Therapy - Pesila Odera; Geoffrey Otieno; Joab Onyango; Bernhards Ogutu; James Owour; Florence Oloo; Martin Ongas; Hulda Swai; Jeremiah Gathirwa (Journal of Nanotechnology)
The World Health Organization recommends artemisinin-based combinations for uncomplicated malaria treatment. Artemether and lumefantrine (LUM) are the first-line treatments, with artemether serving as a prodrug of dihydroartemisinin (DHA), while primaquine (PQ) is primarily used as a prophylactic drug. However, these drugs face challenges such as toxicity, low bioavailability, and poor aqueous solubility. The advent of nanomedicine offers solutions by improving drug pharmacokinetic and pharmacodynamic profiles, thereby enhancing therapeutic efficacy. This study aimed to improve the efficacy of DHA, LUM, and PQ through nanoformulation using solid lipid nanoparticles (SLNs). These nanoparticles were prepared using a modified solvent extraction method based on a water-in-oil-in-water (W/O/W) double emulsion. The resulting nanoparticles had a mean particle size of 357.1 ± 57.14 nm, a polydispersity index of 0.657 ± 0.091, and a zeta potential of −35.7 ± 1.25 mV. The encapsulation efficiencies of DHA, LUM, and PQ were 93.98 ± 0.41%, 42.03 ± 9.46%, and 87.60 ± 0.64%, respectively, with drug loading capacities of 11.87 ± 0.04%, 24.10 ± 2.88%, and 8.01 ± 0.09%. The drugs followed Kors–Peppas and Higuchi drug release models and were released progressively over 68 h. The nanoparticles were spherically shaped, and Fourier transform infrared (FTIR) spectroscopy confirmed the successful nanoformulation process. The nanoformulated drugs demonstrated 30% greater efficacy than conventional oral doses in clearing Plasmodium berghei infection in Swiss albino mice.